Regionalisation of needs to reduce GHG emission from agriculture in Poland - Kistowski, Mariusz (1963– ). Autor; Wiśniewski, Paweł. Autor (IGiPZ PAN, 2020)
An important element in the local shaping of a low-carbon economy, as well as one of the key areas of activity in communal plans for its development should be rural areas and their related agricultural activities. This is due on the one hand to the significant share of agriculture in total greenhouse gas (GHG) emissions in Poland (on average about 8%, locally as much as 20-50%), and on the other hand to the high potential of rural areas to use their resources to increase carbon sequestration in biomass and soil, reduce GHG emissions, as well as use agricultural activity for the development of renewable energy. The paper, based on the results of mathematical modelling of GHG emission from agricultural sources in all Polish communes, attempts to regionalize the needs of integrating agriculture and rural areas into the development of low-carbon economy at the local level. For this purpose, the guiding factors for regionalisation of the needs for mitigation actions were determined, and a regionalisation of these needs as well as a typology of the distinguished regions were, consequently, developed. The regions with the most urgent needs for mitigation actions were indicated, as well as the directions of mitigation actions for particular types of regions.
Keywords: agriculture; rural areas; mitigation of GHG emissions; Polish communes; low-carbon economy